PENGARUH CITRA LEMBAGA, KEPERCAYAAN MAHASISWA TERHADAP KEPUASAN MAHASISWA DAN IMPLIKASINYA KEPADA KOMITMEN RELASIONAL MAHASISWA PADA FAKULTAS EKONOMI UNIVERSITAS NEGERI SEMARANG - H. Sophiyanto, Wuryan; Djoko, Legowo (Jurnal Ilmiah Telaah Manajemen, 2009)
This study is aimed at analyzing the influence of corporate image, students’ trust towards students’ satisfaction and the implication to the students’ relational commitment in Economics Faculty of Semarang State University. It is also conducted to test the direct or indirect influence. The sample used in this study is 97 respondents. It was taken by applying proportional random sampling. There are several findings from this study: (1) the first hypothesis is accepted, which means that there is a significant and positive influence between corporate image towards Economics Faculty students’ satisfaction (beta=0.472); (2) the second hypothesis is accepted indicating that there is a significant and positive influence between students’ trust towards Economics Faculty students’ satisfaction (beta=0.357); (3) the third hypothesis is accepted which shows that there is a significant and positive influence between corporate image towards Economics Faculty students’ relational commitment (beta=0.648); (4) the fourth hypothesis is accepted meaning that there is a significant and positive influence between trust towards Economics Faculty students’ relational commitment (beta=0.186); and (5) the fifth hypothesis is accepted, which means that there is a significant and positive influence between students’ satisfaction towards Economics Faculty students’ relational commitment (beta=0.166). Variable of students’ satisfaction is not a median variable of corporate image towards Economics Faculty students’ relational commitment since the direct influence (0.648) is more than the indirect influence (0.078). Variable of students’ satisfaction is not a median variable of students’ trust towards Economics Faculty students’ relational commitment since the direct influence (0.186) is more than the indirect influence (0.059).Keywords: corporate image, trust, satisfaction, relational commitment.